The Arab Maghreb Union - Finaish, Mohamad; Bell, Eric. (Washington, D.C. : International Monetary Fund, 1994)
The Founding Treaty of the Arab Maghreb Union (AMU), signed in February 1989, calls for a strengthening of all ties among its member states (Algeria, Libya, Mauritania, Morocco, and Tunisia), including a gradual move toward free circulation of goods, services, and factors of production among them. The paper provides an overview of the economic conditions in the AMU member countries, describes the institutional arrangements under the AMU, and assesses the progress made in attaining the economic objectives of the Treaty. In so doing, the paper identifies the main obstacles encountered in making progress toward the objectives of the Treaty and reviews actions that need to be taken to make further progress in the coming years. In that context, the paper also examines the relationship of the AMU countries with the European Union (EU).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet